THE INFLUENCE OF THE APPLICATION OF ENGKLEK ETHNOMATHEMATICS ON MATHEMATICAL PROBLEM SOLVING ABILITY AT MADRASAH TSANAWIYAH NEGERI 6 JAMBI CITY - Arda; Husni El Hilali; Muslimahayati (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Kurikulum Pengembangan Pengajaran dan Pembelajaran (Center of Curriculum Studies, Teaching and Learning Development), 2024)
This study aims to determine the effect of the application of engklek ethnomathematics on mathematical problem-solving abilities in Madrasah Tsanawiyah Negeri 6 Jambi City. This research is a quantitative study with a True experimental design, namely the Posttest-only control design. Class VII population of as many as 113 people. The sampling technique uses Simple Random Sampling. The sample size was drawn using two samples, namely the control group and the experimental group with a research sample of each group totaling 20 students. The data collection technique uses a description test totaling 5 questions. Data analysis in this study used t-test data analysis. From the results of the t-test calculation, it is obtained that t_0 is greater than t_table at a significance level of 5% or 1%, for a party test a significant level is 5% = 4,711 > 2.03 and a party test a significant level is 1% = 4,711 > 2.03. From the calculation results, the researchers found that the application of crank ethnomathematics had an effect on students' mathematical problem-solving abilities at MTs N 6 Jambi City. The results of this study suggest teachers be able to apply culture-based learning media in mathematics lessons.